Gaya Hidup Gamer Online: Pengguna Voucher Top UP Garena - Muhammad Rahman Febliansa; Tri Febrina Melinda; Desti Rupita Sari (UNIVED Press, 2022)
The purpose of this study is to investigate discusses the life style of Gamer Online used Garena voucher in Bengkulu city. The research was conducted by using questionnaires. The quistionnaires were distributed to the 300 respondent who used Garena voucher. In the data analisys, approach used qualitative descriptive. This study used purposive sampling as method. Based on the mean analysis of the VLAM is four dimensions of live style on respondent, the obtained results that are categorized as having a very high value categories. They, must to do inovation of voucher Garena design but, them should keep other aspect such as, social marketing. Therefore, the better implemented by shops, it will provide a better impact toward outlet purchase Garena Voucher of Bengkulu city.